Early Christian-Muslim debate on the unity of God : three Christian scholars and their engagement with Islamic thought (9th century c.e.) - Husseini, Sara Leila. (The History of Christian-Muslim Relations, 2014)
Early Christian-Muslim Debate on the Unity of God examines the writings of three of the earliest known Christian theologians to write comprehensive theological works in Arabic. Theodore Abū Qurra, Abū Rā'iṭa and 'Ammār al-Baṣrī provide valuable insight into early Christian-Muslim debate shortly after the rise of the Islamic empire. Through close examination of their writings on the doctrine of the Trinity, Sara Husseini demonstrates the creativity of these theologians, who make use of language, style and argumentation characteristic of Islamic theological thought (kalām), in order to help articulate their long-established religious truths. Husseini offers close analysis of the authors individually and comparatively, exploring their engagement with Islamic theology and their role in this fascinating period.